Microtubules and cyclic amp in human leukocytes: on the order of things - Malawista, SE (The Rockefeller University Press, 1978)
We have shown previously that the β-adrenergic agonist isoproterenol (2μM) and the phosphodiesterase inhibitor isobutylmethylxanthine (1 mM) produce a much greater increase in cyclic AMP in human leukocytes that have been pretreated with colchicine (or with other agents that affect microtubule assembly) than in control leukocytes. The effects of colchicines were both time- and dose-dependant. These and other data suggested that the generation of cyclic AMP is normally restricted by an intact system of cytoplasmic microtubules. If so, then the same time and dose dependencies might apply to other colchicines-induced changes in leukocyte function. We have now assayed the distribution of concanavalin A (Con A)-receptor complexes on the leukocyte membrane, taking into account that leukocytes competent to assemble microtubules show a uniform distribution of surface- bound Con A whereas microtubule-deficient cells accumulate Con A in surface caps. We have found that the effect of colchicine on capping is also both time- and dose dependent, and that the dose-response relationships conform to those required to increase cyclic AMP levels. These findings provide further evidence that both colchicine-induced Con-A capping and colchicine- induced cyclic AMP generation depend upon the relaxation of constraints normally imposed by cytoplasmic microtubules upon the plasma membrane, which limit, respectively, lateral mobility of the lectin-receptor complexes, and expression of hormone-sensitive adenylate cyclase. Moreover, colchicine-induced Con-A cap formation is not affected even by very large changes in leukocyte cyclic AMP levels. Thus, elevated cyclic AMP levels do not appear to promote the dissolution of microtubules; rather, the dissolution of microtubules permits the generation of increased amounts of cyclic AMP.